The Activity of Gold Nanoparticles Synthesized Using Helichrysum odoratissimum Against Cutibacterium acnes Biofilms - De Canha, Marco Nuno; Thipe, Velaphi Clement; Katti, Kattesh V.; Mandiwana, Vusani; Kalombo, Michel Lonji; Ray, Suprakas Sinha; Rikhotso, Rirhandzu; Janse van Vuuren, Arno; Lall, Namrita (Frontiers in Cell and Developmental Biology, 2021)
The human skin is home to millions of bacteria, fungi and viruses which form part of a unique microbiome. Commensal microbes, including Cutibacterium acnes can occasionally become opportunistic resulting in the onset of dermatological diseases such as acne. Acne is defined as a chronic inflammatory disorder based on its ability to persist for long periods throughout an individual’s life. The synthesis of gold nanoparticles (AuNPs) was performed using the bottom-up approach by reduction of a gold salt (HAuCl4.3H2O) by the methanol extract (HO-MeOH) and aqueous decoction prepared from the dried aerial parts of H. odoratissimum (HO-Powder). The HO-MeOH and HO-Powder AuNPs were prepared as unstabilised (-GA) or stabilised (+GA) by the omission or addition of Gum Arabic (GA) as the capping agent. The characterization of the AuNPs was performed using Transmission Electron Microscopy (TEM), dynamic light scattering (DLS), Ultraviolet-Visual spectroscopy (UV-Vis), Thermogravimetric Analysis (TGA), X-Ray Diffraction (XRD) and Zeta-potential. The MBIC50 values for HO-MeOH – GA and HO-MeOH + GA were 1.79 ± 0.78%v/v and 0.22 ± 0.16%v/v, respectively. The HO-Powder AuNPs showed potent inhibition of C. acnes cell adhesion to the 96-well plates. The HO-MeOH – GA and HO-Powder + GA exhibited IC50 of 22.01 ± 6.13%v/v and 11.78 ± 1.78%v/v, respectively. The activity of the AuNPs validated the anti-adhesion activity of the methanol extract in the crude form. The study emphasizes the selectivity of H. odoratissimum AuNPs for the prevention of C. acnes cell adhesion and not antimicrobial activity, which may prevent the emergence of resistant strains of C. acnes through reduced bactericidal or bacteriostatic activity, while targeting mechanisms of pathogenesis.